HACKER LE CAPITALISME: Technocritique de l'innovation numérique. - Fourmentraux, Jean-Paul (Études Digitales, 2020)
The article presents information related to hacking; and technocriticism of digital innovation s. It mentions about the democratization of the information technology (IT) and internet development; and also talks about the re-materializing of the logics and protocols buried in the guts of algorithms, neural networks and artificial intelligence.